Manufacturing method for negative electrode for zinc secondary battery

By uniformly coating the material layer on both sides of the negative electrode container of the zinc battery and controlling the thickness ratio of the material layer between 0.7 and 1, the problem of morphology changes and uneven charging and discharge distribution during the charging and discharge process of the zinc battery is solved, and the excellent life performance of the zinc battery is achieved.

JP2025061537AActive Publication Date: 2025-04-10ENERGYWITH CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2025008377
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-10
Estimated Expiration
2039-04-04

AI Technical Summary

Technical Problem

The negative electrodes of existing zinc batteries are prone to dissolution and precipitation of zinc hydroxide during the charging and discharging process, resulting in changes in the morphology of the negative electrode, uneven charging and discharging distribution and the growth of zinc dendrites, which in turn causes short circuit problems and affects the life performance of zinc batteries.

Method used

A method of manufacturing a negative electrode is adopted to ensure the uniformity of the material layer and the relative thickness matching of the material layer are ensured by uniformly coating the negative electrode material layer on both sides of the negative electrode container and controlling the thickness ratio of the material layer on both sides during the manufacturing process.

Benefits of technology

Through this method, it is possible to effectively prevent uneven precipitation of zinc oxygen, maintain the uniform state of the negative electrode, reduce the uneven phenomenon during the charging and discharging process, and extend the service life of the zinc battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061537000001_ABST
    Figure 2025061537000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method for a negative electrode for a zinc battery, which can have excellent life performance.SOLUTION: A manufacturing method for a negative electrode for a zinc battery including a negative electrode current collector 21, a first negative electrode material layer provided on one surface 21a of the negative electrode current collector, and a second negative electrode material layer provided on the other surface 21b of the negative electrode current collector 21 includes a negative electrode material layer forming step of forming the first negative electrode material layer and the second negative electrode material layer in such a way that the negative electrode current collector 21 is transmitted between a first wall surface 51 and a second wall surface 52 while negative electrode material pastes 23a, 23b on both surfaces are brought into contact with the first wall surface 51 and the second wall surface 52 facing each other with the negative electrode material pastes 23a, 23b adhering to both surfaces of the negative electrode current collector 21. In the negative electrode material layer forming step, a ratio of a distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 to a distance D1 between the first wall surface 51 and the one surface 21a of the negative electrode current collector 21 is 0.7 to 1.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a negative electrode for a zinc battery, and a negative electrode for a zinc battery. [Background technology]

[0002] Known zinc batteries include nickel-zinc batteries, air-zinc batteries, and silver-zinc batteries. For example, nickel-zinc batteries are aqueous batteries that use an aqueous electrolyte such as an aqueous potassium hydroxide solution, and therefore are highly safe. In addition, the combination of zinc electrodes and nickel electrodes is known to provide a high electromotive force for an aqueous battery. Furthermore, nickel-zinc batteries have excellent input / output performance and low cost, and therefore their applicability to industrial applications (e.g., backup power sources, etc.) and automotive applications (e.g., hybrid vehicles, etc.) is being considered.

[0003] The charge and discharge reactions of a nickel-zinc battery proceed, for example, according to the following formula (discharge reaction: to the right, charge reaction: to the left). (Positive electrode)2NiOOH+2H2O+2e - → 2Ni(OH)2+2OH - (Negative electrode) Zn+2OH - → Zn(OH)2+2e -

[0004] As shown in the above formula, in zinc batteries, zinc hydroxide (Zn(OH)2) is produced by the discharge reaction. Zinc hydroxide is soluble in the electrolyte, and when zinc hydroxide dissolves in the electrolyte, it becomes zinc tetrahydroxide ions ([Zn(OH)4]2 -) diffuses into the electrolyte. As a result, the negative electrode undergoes a morphological change (deformation) and the distribution of the charging current becomes uneven, causing zinc to precipitate locally on the negative electrode, resulting in the formation of dendrites (branched crystals). In conventional zinc batteries, when dendrites grow due to repeated charging and discharging, the dendrites may penetrate the separator and cause a short circuit. For this reason, various attempts have been made to prevent such short circuits caused by dendrites and improve the life performance. For example, the following Patent Document 1 discloses a technology for preventing short circuits caused by dendrites by interposing a nickel-plated nonwoven fabric between the electrodes. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Unexamined Patent Publication No. 58-126665 Summary of the Invention [Problem to be solved by the invention]

[0006] Thus, there is a demand for further improvement in the life performance of zinc batteries.

[0007] An object of one aspect of the present invention is to provide a method for producing a zinc battery anode that can provide excellent life performance, and a zinc battery anode. [Means for solving the problem]

[0008] One aspect of the present invention provides a method for producing a zinc battery anode comprising a negative electrode collector, a first negative electrode material layer provided on one side of the negative electrode collector, and a second negative electrode material layer provided on the other side of the negative electrode collector, the method comprising a negative electrode material layer forming step of forming the first and second negative electrode material layers by passing the negative electrode collector between the first and second wall surfaces while contacting the negative electrode material paste on both sides of the negative electrode collector with the first and second wall surfaces facing each other, in which the ratio of the distance between the first wall surface and one side of the negative electrode collector to the distance between the second wall surface and the other side of the negative electrode collector in the negative electrode material layer forming step is 0.7 to 1. A zinc battery using the zinc battery anode obtained by this method has excellent life performance.

[0009] In one aspect, the above ratio may be less than one.

[0010] In one aspect, the difference between the distance between the first wall surface and one surface of the negative electrode current collector and the distance between the second wall surface and the other surface of the negative electrode current collector is preferably 0.03 mm or less.

[0011] Another aspect of the present invention provides a zinc battery anode comprising a negative electrode current collector, a first negative electrode material layer provided on one side of the negative electrode current collector, and a second negative electrode material layer provided on the other side of the negative electrode current collector, wherein the ratio of the thickness of the second negative electrode material layer to the thickness of the first negative electrode material layer is 0.7 to 1. A zinc battery using this zinc battery anode has excellent life performance.

[0012] In another aspect, the ratio may be less than one.

[0013] In another aspect, the difference between the thickness of the first negative electrode material layer and the thickness of the second negative electrode material layer is preferably 0.03 mm or less. Effect of the Invention

[0014] According to one aspect of the present invention, it is possible to provide a method for manufacturing a zinc battery anode capable of obtaining excellent life performance, and a zinc battery anode. [Brief description of the drawings]

[0015] [Figure 1] 1 is a micrograph showing the cross-section of a conventional double-sided coated negative electrode over the number of battery cycles. [Diagram 2] FIG. 2 is a schematic diagram showing an example of an apparatus used in a method for producing a zinc battery negative electrode according to one embodiment. [Diagram 3] 3 is a schematic cross-sectional view showing a layer forming section in the apparatus shown in FIG. 2. [Figure 4] FIG. 4 is a plan view showing an example of a measurement location of the thickness of a negative electrode layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the following embodiments, and can be practiced with various modifications within the scope of the gist. The sizes of the components in each figure are conceptual, and the relative relationships between the sizes of the components are not limited to those shown in each figure.

[0017] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. In this specification, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In addition, in this specification, the term "layer" includes a structure having a shape formed on the entire surface when observed as a plan view, as well as a structure having a shape formed on a part of the surface. In addition, in this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended effect of the process is achieved.

[0018] The negative electrode obtained by the manufacturing method according to the following embodiment is a negative electrode (negative electrode for zinc battery) used in a zinc battery. Examples of zinc batteries (e.g., zinc secondary batteries) include nickel-zinc batteries, air-zinc batteries, and silver-zinc batteries. The basic structure of a zinc battery can be the same as that of a conventional zinc battery. The zinc battery in this specification may be either chemically formed or unchemically formed.

[0019] A method for manufacturing a negative electrode for a zinc battery according to one embodiment includes a negative electrode collector, a first negative electrode material layer provided on one side of the negative electrode collector, and a second negative electrode material layer provided on the other side of the negative electrode collector. The method includes a negative electrode material layer forming step of forming a first negative electrode material layer and a second negative electrode material layer by passing the negative electrode collector between the first wall surface and the second wall surface while contacting the negative electrode material paste on both sides with the first wall surface and the second wall surface facing each other, with the negative electrode material paste adhered to both sides of the negative electrode collector. In the negative electrode material layer forming step, the ratio of the distance between the first wall surface and one side of the negative electrode collector to the distance between the second wall surface and the other side of the negative electrode collector is 0.7 to 1.

[0020] In addition, the negative electrode for a zinc battery according to one embodiment is a negative electrode for a zinc battery comprising a negative electrode current collector, a first negative electrode material layer provided on one side of the negative electrode current collector, and a second negative electrode material layer provided on the other side of the negative electrode current collector, in which the ratio of the thickness of the second negative electrode material layer to the thickness of the first negative electrode material layer is 0.7 to 1.

[0021] By using the zinc battery negative electrode according to these embodiments, it is possible to obtain excellent life performance in the zinc battery. Although the reason why such an effect is obtained is not clear, the inventors speculate as follows.

[0022] In the negative electrode for zinc batteries (hereinafter simply referred to as the "negative electrode"), the negative electrode active material, metallic zinc, is converted into tetrahydroxide zincate ions ([Zn(OH)4]2 - ) is eluted as [Zn(OH)4]2 - is supersaturated in the electrolyte and precipitates as zinc oxide (ZnO) on the negative electrode layer. Here, [Zn(OH)4]2 - The concentration of ZnO and the amount of ZnO precipitated are considered to be affected by the thickness of the negative electrode layer. When the negative electrode layer is thick, [Zn(OH)4]2 -The concentration of ZnO increases, and therefore, when the negative electrode layer is thick, the amount of ZnO deposited on the negative electrode layer also increases. Since ZnO is slightly soluble in the electrolyte, the [Zn(OH)4]2 - exists in a supersaturated state, which further promotes the precipitation of ZnO.

[0023] There are negative electrodes, so-called double-sided coated negative electrodes, in which a negative electrode material layer is provided on each side of a current collector. As described above, the amount of ZnO precipitation increases as the thickness of the negative electrode material layer increases, so in a double-sided coated negative electrode, if there is a large difference in thickness between the negative electrode material layer on one side and the negative electrode material layer on the other side, an environment is created in which ZnO is likely to be precipitated unevenly on the surface of the thicker negative electrode material layer, and further, as the number of cycles of the battery increases, the difference in thickness between the front and back of the same negative electrode increases.

[0024] FIG. 1 is a micrograph (scanning electron microscope, 200x magnification) of a cross section of a conventional double-sided coated negative electrode, which shows the state of the cross section of the negative electrode as the number of cycles of the battery increases. FIG. 1(a) shows the state of the negative electrode before use, and the number of cycles increases in the order of FIG. 1(b), FIG. 1(c), and FIG. 1(d). In the double-sided coated negative electrode 10 shown in FIG. 1, as shown in FIG. 1(a), there is a difference in thickness between the first negative electrode material layer 12 provided on one side of the negative electrode current collector 11 and the second negative electrode material layer 13 provided on the other side of the negative electrode current collector 1. That is, the first negative electrode material layer 12 is thicker than the second negative electrode material layer 13. In such a negative electrode 10, as shown in FIG. 1(b) to FIG. 1(d), the difference in thickness between the first negative electrode material layer 12 and the second negative electrode material layer 13 increases as the number of cycles increases. This is believed to be because, for the reasons mentioned above, the thicker the negative electrode material layer is, the more unevenly ZnO is precipitated.

[0025] In zinc batteries, hydroxide ions (OH), which are charge carriers, are transported between the positive and negative electrodes, which face each other through a separator such as a microporous membrane or nonwoven fabric. - As shown in Figure 1, if one of the negative electrode layers loses weight unevenly, smooth OH diffusion with the opposing positive electrode is prevented. -It is believed that the charge / discharge reaction is inhibited because the exchange of charge and discharge is prevented.

[0026] More specifically, in the discharge reaction, OH diffused from the positive electrode - Since the negative electrode consumes OH, the active material in the negative electrode layer facing the positive electrode can react most smoothly. However, if the negative electrode layer facing the positive electrode is reduced in weight, - The need for diffusion to the active material in the negative electrode layer on the opposite side of the positive electrode through the negative electrode current collector such as punched metal increases. This increases the diffusion resistance, and it is presumed that the discharge capacity is gradually impaired. In addition, the charge reaction is a reaction in the opposite direction to the discharge reaction, and OH is released from the negative electrode to the positive electrode. - Therefore, when the negative electrode layer facing the positive electrode is reduced in weight, the charge capacity is impaired due to an increase in diffusion resistance, as in the discharge reaction. If the charge capacity is impaired, it is thought that the decrease in discharge capacity will be further accelerated.

[0027] On the other hand, in the negative electrode obtained by the manufacturing method according to the present embodiment, the difference in thickness between the first negative electrode material layer provided on one side of the negative electrode current collector and the second negative electrode material layer provided on the other side of the negative electrode current collector is small, so that it is possible to suppress the deposition of ZnO unevenly on one of the negative electrode material layers. - This allows the transfer of charge and discharge reactions to be prevented from being hindered. As a result, it is believed that the life performance of zinc batteries can be improved.

[0028] <Method of manufacturing zinc battery negative electrode> A method for manufacturing a negative electrode for a zinc battery according to one embodiment includes a negative electrode material layer formation step of forming a first negative electrode material layer and a second negative electrode material layer by passing the negative electrode current collector between the first wall surface and the second wall surface while contacting the negative electrode material paste on both sides of the negative electrode current collector with a first wall surface and a second wall surface facing each other, with the negative electrode material paste adhered to both sides of the negative electrode current collector.

[0029] The negative electrode current collector has a shape such as a flat plate or a sheet. The negative electrode current collector may be a three-dimensional mesh-structured current collector made of foam metal, expanded metal, punching metal, felt-like metal fiber, or the like. The negative electrode current collector is made of a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the negative electrode (a material having an oxidation-reduction potential more noble than the reaction potential of the negative electrode, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize the material) can be used. In addition, in the negative electrode, a decomposition reaction of the electrolyte proceeds as a side reaction to generate hydrogen, and a material with a high hydrogen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials constituting the negative electrode current collector include zinc, lead, tin, and metal materials plated with metal such as tin (copper, brass, steel, nickel, etc.).

[0030] The negative electrode material paste is a paste containing components constituting the negative electrode material layer. The negative electrode material paste may be, for example, a paste obtained by adding the components constituting the negative electrode material layer to a dispersion medium such as water and kneading them.

[0031] The negative electrode material paste contains a negative electrode active material containing zinc. Examples of the negative electrode active material include metallic zinc, zinc oxide, zinc hydroxide, etc. For example, the negative electrode material paste contains metallic zinc in a fully charged state, and contains zinc oxide and zinc hydroxide in an end-of-discharge state.

[0032] The amount of the negative electrode active material is preferably in the following range based on the total mass of the non-volatile content of the negative electrode paste (components excluding the dispersion medium from the negative electrode paste). From the viewpoint of easily achieving both excellent life performance and discharge performance, the amount of the negative electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 75 mass% or more. From the viewpoint of easily achieving both excellent life performance and discharge performance, the amount of the negative electrode active material is preferably 95 mass% or less, more preferably 90 mass% or less, and even more preferably 85 mass% or less. From these viewpoints, the amount of the negative electrode active material is preferably 50 to 95 mass%.

[0033] The negative electrode material paste may contain additives other than the negative electrode active material. Examples of the additives include a binder and a conductive agent. Examples of the binder include polytetrafluoroethylene, hydroxyethyl cellulose, polyethylene oxide, polyethylene, and polypropylene. The amount of the binder may be, for example, 0.5 to 10 parts by mass per 100 parts by mass of the negative electrode active material. Examples of the conductive agent include an indium compound (such as indium oxide). The amount of the conductive agent may be, for example, 1 to 20 parts by mass per 100 parts by mass of the negative electrode active material.

[0034] Fig. 2 is a schematic diagram showing an example of an apparatus used in the manufacturing method of the zinc battery negative electrode according to the present embodiment. The zinc battery negative electrode according to the present embodiment can be manufactured, for example, by using the apparatus shown in Fig. 2.

[0035] In this manufacturing method, first, the roll-shaped negative electrode collector 21 is unwound by the unwinding section 30, and then the negative electrode collector 21 is passed through a tank 40 in which a negative electrode material paste is placed, thereby adhering the negative electrode material paste to the negative electrode collector 21. In this manufacturing method, the roll-shaped negative electrode collector 21 is unwound by the unwinding section 30, but a flat or sheet-shaped negative electrode collector may be prepared and placed in the tank 40. Next, the negative electrode collector is pulled up from the tank 40. The negative electrode material paste is attached to both sides (one side and the other side of the negative electrode collector 21) of the pulled up negative electrode collector 21. This allows the negative electrode collector 22 with the negative electrode material paste attached to both sides to be obtained. In the negative electrode collector 22 with the negative electrode material paste attached to both sides, the negative electrode material paste may be attached to a part of one side and the other side of the negative electrode collector 21, or may be attached to the entire surface.

[0036] Next, the negative electrode current collector 22 with the negative electrode material paste applied to both sides thereof is passed through a layer forming section 50 .

[0037] 3 is a schematic cross-sectional view showing the layer forming section 50 in the apparatus shown in FIG. 2. The layer forming section 50 has a gap 53 formed by a first wall surface 51 and a second wall surface 52 facing each other. The negative electrode current collector 22 having the negative electrode material paste attached to both sides thereof is passed through the gap 53 in the direction of the arrow. At this time, the negative electrode material paste 23a attached to one side 21a of the negative electrode current collector 21 is brought into contact with the first wall surface 51, and the negative electrode material paste 23b attached to the other side 21b of the negative electrode current collector 21 is brought into contact with the second wall surface 52, while the negative electrode current collector 22 having the negative electrode material paste attached to both sides thereof is passed through the gap 53.

[0038] Immediately after being pulled out of the tank 40 (before passing through the layer forming section 50), the negative electrode current collector 22 with the negative electrode material paste attached to both sides may have unevenness on the surface of the negative electrode material paste or unevenness in the amount of the negative electrode material paste attached, as shown in Fig. 3. By passing the negative electrode current collector 22 through the layer forming section 50 while contacting the first wall surface 51 and the second wall surface 52 of the layer forming section 50, the unevenness on the surfaces of the negative electrode material pastes 23a and 23b can be made uniform.

[0039] In the manufacturing method of this embodiment, the ratio (D2 / D1) of the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 to the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 is 0.7 to 1. This makes it possible to obtain a negative electrode having a small difference in thickness between the first negative electrode material layer finally formed on one surface 21a of the negative electrode current collector 21 and the second negative electrode material layer finally formed on the other surface 21b of the negative electrode current collector 21. The distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 is longer than the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21, or is the same as the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21.

[0040] From the viewpoint of easily obtaining a zinc battery negative electrode having excellent life performance, the distance ratio (D2 / D1) is preferably 0.8 or more, more preferably 0.9 or more, and even more preferably 0.95 or more. The distance ratio (D2 / D1) is particularly preferably 1, but may be less than 1.

[0041] The ratio of the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 to the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 can be adjusted by adjusting the position in the gap 53 through which the negative electrode current collector 21 passes.

[0042] The difference between the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 and the distance D2 between the first wall surface 51 and the other surface 21b of the negative electrode current collector 21 is preferably 0.03 mm or less, more preferably 0.02 mm or less, and even more preferably 0.01 mm or less, from the viewpoint of easily obtaining a zinc battery negative electrode having excellent life performance. It is particularly preferable that the difference between the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 and the distance D2 between the first wall surface 51 and the other surface 21b of the negative electrode current collector 21 is 0, but it may be greater than 0.

[0043] From the viewpoint of ensuring a charge reserve (capacity that can be excessively charged on the negative electrode side), the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21, and the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 are each preferably 0.2 mm or more, more preferably 0.3 mm or more, and even more preferably 0.35 mm or more. From the viewpoint of ensuring an energy density, the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21, and the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 are each preferably 0.5 mm or less, more preferably 0.45 mm or less, and even more preferably 0.4 mm or less.

[0044] The distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21, and the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 can be adjusted, for example, by a gap adjustment unit 54 provided in the layer forming unit 50. The gap adjustment unit 54 can change the positions of the first wall surface 51 and the second wall surface 52, and can adjust the size of the gap 53. As a result, the size of the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21, and the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 are also adjusted. The method of adjusting the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21, and the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 is not limited to this.

[0045] 2, the negative electrode current collector 22 having the negative electrode material paste attached to both sides thereof after passing through the layer forming unit 50 is passed through a drying furnace 60. Examples of the drying furnace 60 include a reduced pressure drying furnace and a drying furnace equipped with an infrared heater.

[0046] The temperature inside the drying oven 60 may be, for example, 90° C. or more, 100° C. or more, or 110° C. or more, and may be 150° C. or less, 140° C. or less, or 130° C. or less. The time for passing through the drying oven 60 (drying time) may be, for example, 1 minute or more, 3 minutes or more, or 5 minutes or more, and may be 60 minutes or less, 30 minutes or less, or 20 minutes or less.

[0047] By passing through the drying furnace 60, the dispersion medium contained in the negative electrode material paste volatilizes, and a first negative electrode material layer is formed on one side of the negative electrode current collector 21, and a second negative electrode material layer is formed on the other side, to obtain an unformed negative electrode 24. The continuously manufactured negative electrodes 24 as shown in FIG. 2 can be cut to a predetermined size and used for manufacturing zinc batteries.

[0048] The method for manufacturing a zinc battery negative electrode according to the embodiment described above can be modified in various ways.

[0049] For example, in the method for manufacturing a negative electrode for a zinc battery, the method for attaching the negative electrode material paste to the negative electrode current collector may be application with an applicator or the like. Alternatively, a negative electrode current collector to which the negative electrode material paste has already been attached may be prepared.

[0050] The layer forming section may include two separate members, and the negative electrode current collector having the negative electrode material paste applied thereto may be passed between the two separate members while the negative electrode material paste is brought into contact with the wall surfaces of each of the two separate members.

[0051] After the negative electrode current collector with the negative electrode material paste applied to both sides is passed through the layer forming section, pressing or the like may be performed as necessary, thereby obtaining a negative electrode with an increased density of the negative electrode material layer.

[0052] In the method for drying the negative electrode material paste, a drying furnace may not be used, and the negative electrode current collector on which the layer of the negative electrode material paste has been formed may be left stationary in a room temperature environment, for example.

[0053] In the above-described embodiment, an apparatus capable of manufacturing a zinc battery negative electrode through a series of steps as shown in FIG. 2 was used, but the steps of attaching the negative electrode material paste to the negative electrode current collector, passing the negative electrode material paste through a layer forming section, and drying the negative electrode material paste may be performed in separate apparatuses.

[0054] <Zinc battery anode> The zinc battery negative electrode according to one embodiment includes a first negative electrode material layer provided on one side of a negative electrode current collector and a second negative electrode material layer provided on the other side of the negative electrode current collector, and the ratio of the thickness of the second negative electrode material layer to the thickness of the first negative electrode material layer is 0.7 to 1. The zinc battery negative electrode may be either chemically formed or unformed. The unformed zinc battery negative electrode can be obtained, for example, by the manufacturing method for the zinc battery negative electrode described above.

[0055] The embodiment of the negative electrode current collector may be the same as the embodiment of the negative electrode current collector in the above-mentioned method for producing a zinc battery negative electrode.

[0056] The negative electrode material layer contains a negative electrode active material containing zinc. The form of the negative electrode active material may be the same as the negative electrode active material contained in the negative electrode material paste described above. In addition to the negative electrode active material, the negative electrode material layer may also contain the above-mentioned additives.

[0057] In this specification, the "thickness of the negative electrode material layer" refers to the distance between one surface of the negative electrode current collector and the surface of the negative electrode material layer provided on the one surface opposite to the negative electrode current collector, and means the average value measured at nine points on the negative electrode material layer. The nine measurement points may be the upper left corner, upper center, upper right corner, left center, center, right center, lower left corner, lower center, and lower right center when the negative electrode is viewed from the stacking direction. FIG. 4 is a plan view showing an example of the measurement points of the thickness of the negative electrode material layer. As shown in FIG. 4, the thickness of the negative electrode material layer 25 provided on the negative electrode current collector 21 is measured at nine points, the upper left corner a, the upper center b, the upper right corner c, the left center d, the center e, the right center f, the lower left corner g, the lower center h, and the lower right center i, and can be the average value of those measured values. The thickness at each point of the negative electrode can be measured using, for example, a micrometer.

[0058] The ratio of the thickness of the second negative electrode material layer to the thickness of the first negative electrode material layer (thickness of the second negative electrode material layer / thickness of the first negative electrode material layer) is preferably 0.8 or more, more preferably 0.9 or more, and even more preferably 0.95 or more, from the viewpoint of easily obtaining a zinc battery negative electrode having excellent life performance. The thickness ratio (thickness of the second negative electrode material layer / thickness of the first negative electrode material layer) is particularly preferably 1, but may be less than 1. The thickness of the first negative electrode material layer is thicker (larger) than the thickness of the second negative electrode material layer, or is the same thickness as the second negative electrode material layer.

[0059] From the viewpoint of easily obtaining a zinc battery negative electrode having excellent life performance, the difference in thickness between the first negative electrode layer and the second negative electrode layer is preferably 0.03 mm or less, more preferably 0.02 mm or less, and even more preferably 0.01 mm or less. It is particularly preferable that the difference in thickness between the first negative electrode layer and the second negative electrode layer is 0, but it may be greater than 0.

[0060] From the viewpoint of ensuring charge reserve, the thickness of the first negative electrode material layer and the thickness of the second negative electrode material layer are each preferably 0.2 mm or more, more preferably 0.3 mm or more, and even more preferably 0.35 mm or more. From the viewpoint of ensuring energy density, the thickness of the first negative electrode material layer and the thickness of the second negative electrode material layer are each preferably 0.6 mm or less, more preferably 0.5 mm or less, and even more preferably 0.4 mm or less. The thickness of the first negative electrode material layer and the thickness of the second negative electrode material layer may correspond to the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 and the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 in the above-mentioned manufacturing method, respectively.

[0061] <Zinc battery> Hereinafter, a nickel-zinc battery will be described as an example of the zinc battery according to the present embodiment. The nickel-zinc battery according to one embodiment includes, for example, a battery case, an electrolyte, and an electrode group (for example, an electrode plate group). The electrode group and the electrolyte are contained in the battery case.

[0062] The electrode group is composed of, for example, a separator, and a positive electrode (such as a positive electrode plate) and a negative electrode (such as a negative electrode plate) that face each other through the separator. In the electrode group, the positive electrodes and the negative electrodes are connected to each other, for example, by a strap. The negative electrode may be the zinc battery negative electrode according to the above-mentioned embodiment.

[0063] The positive electrode includes, for example, a positive electrode current collector, a first positive electrode material layer provided on one surface of the positive electrode current collector, and a second positive electrode material layer provided on the other surface of the positive electrode current collector. The positive electrode may be either before or after chemical formation.

[0064] The positive electrode collector has a shape such as a flat plate or a sheet. The positive electrode collector may be a three-dimensional mesh-structured collector made of foamed metal, expanded metal, punched metal, felt-like metal fiber, or the like. The positive electrode collector is made of a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the positive electrode (a material having an oxidation-reduction potential more noble than the reaction potential of the positive electrode, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize the material) can be used as such a material. In addition, in the positive electrode, a decomposition reaction of the electrolyte proceeds as a side reaction to generate oxygen gas, and a material with a high oxygen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the positive electrode collector include platinum; nickel (foamed nickel, etc.); and metal materials (copper, brass, steel, etc.) plated with a metal such as nickel. Among these, a positive electrode collector made of foamed nickel is preferably used. From the viewpoint of further improving the high rate discharge performance, it is preferable that at least the portion of the positive electrode current collector that supports the positive electrode material (positive electrode material supporting portion) is made of foamed nickel.

[0065] The positive electrode layer contains a positive electrode active material containing nickel. Examples of the positive electrode active material include nickel oxyhydroxide (NiOOH) and nickel hydroxide. The positive electrode layer contains, for example, nickel oxyhydroxide in a fully charged state and nickel hydroxide in an end-of-discharge state. The content of the positive electrode active material may be, for example, 50 to 95 mass% based on the total mass of the positive electrode layer.

[0066] The positive electrode layer may further contain, as an additive, a component other than the positive electrode active material, such as a binder, a conductive agent, an expansion inhibitor, etc.

[0067] Examples of the binder include hydrophilic or hydrophobic polymers. Specifically, for example, carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), sodium polyacrylate (SPA), fluorine-based polymers (polytetrafluoroethylene (PTFE) and the like) can be used as the binder. The content of the binder is, for example, 0.01 to 5 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0068] The conductive agent may be a cobalt compound (metallic cobalt, cobalt oxide, cobalt hydroxide, etc.), etc. The content of the conductive agent is, for example, 1 to 20 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0069] The expansion inhibitor may be zinc oxide, etc. The content of the expansion inhibitor is, for example, 0.01 to 5 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0070] The separator may be, for example, a separator having a shape such as a flat plate or a sheet. Examples of the separator include a polyolefin-based microporous membrane, a nylon-based microporous membrane, an oxidation-resistant ion-exchange resin membrane, a cellophane-based regenerated resin membrane, an inorganic-organic separator, and a polyolefin-based nonwoven fabric. The separator may be processed into a bag shape so that the positive electrode and / or the negative electrode can be accommodated. In this case, the positive electrode and / or the negative electrode may be accommodated in the separator. The separator may be used alone or in combination of two or more types.

[0071] The manufacturing method of the nickel-zinc battery described above includes a component manufacturing process for obtaining components of the zinc battery, and an assembly process for assembling the components to obtain the zinc battery. In the component manufacturing process, at least electrodes (positive and negative electrodes) are obtained. The manufacturing method of the negative electrode is the manufacturing method of the negative electrode for the zinc battery described above.

[0072] The positive electrode is made of a positive electrode material paste obtained by adding a dispersion medium (e.g., water) to the raw material of the positive electrode layer and kneading the mixture. The method for obtaining the positive electrode includes, for example, the same method as the above-mentioned method for producing a negative electrode for a zinc battery, and a method in which the positive electrode material paste is applied to or immersed in a positive electrode current collector and then dried.

[0073] In the assembly process, for example, the positive and negative electrodes obtained in the component manufacturing process are alternately stacked with separators between them, and then the positive and negative electrodes are connected to each other with straps to form an electrode group. Next, this electrode group is placed in a battery case, and a lid is attached to the top of the battery case to obtain an unformed zinc battery (nickel-zinc battery).

[0074] Next, the electrolyte is poured into the battery case of the unformed zinc battery and then left for a certain period of time. Then, the zinc battery (nickel-zinc battery) is obtained by forming the battery by charging under predetermined conditions. The forming conditions can be adjusted according to the properties of the positive and negative electrode active materials.

[0075] The above describes an example of a nickel-zinc battery (e.g., a nickel-zinc secondary battery) in which the positive electrode is a nickel electrode, but the zinc battery may also be an air-zinc battery (e.g., an air-zinc secondary battery) in which the positive electrode is an air electrode, or a silver-zinc battery (e.g., a silver-zinc secondary battery) in which the positive electrode is a silver oxide electrode. EXAMPLES

[0076] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0077] Example 1 <Preparation of negative electrodes for zinc batteries> A negative electrode paste was prepared by weighing and mixing zinc oxide, metallic zinc, bismuth oxide, hydroxyethyl cellulose, and ion-exchanged water in predetermined amounts, and stirring the resulting mixture. At this time, the mass ratio of the non-volatile content in the negative electrode paste was adjusted to "zinc oxide: metallic zinc: bismuth oxide: hydroxyethyl cellulose = 72: 20.5: 5: 2.5". AV-15F (product name) manufactured by Sumitomo Seika Chemicals Co., Ltd. was used as the hydroxyethyl cellulose. The moisture content of the negative electrode paste was adjusted to 20.5 mass% based on the total mass of the negative electrode paste.

[0078] A zinc battery negative electrode was manufactured using the device shown in FIG. 2. A roll-shaped negative electrode current collector (copper punching metal) was set in the unwinding section 30. The negative electrode current collector was passed through a tank 40 containing a negative electrode material paste, and the negative electrode material paste was attached to both sides of the negative electrode current collector. Next, the negative electrode current collector with the negative electrode material paste attached was passed through a layer forming section 50. At this time, the width of the gap 53 in the layer forming section 50 and the position where the negative electrode current collector passed were adjusted so that the distance D1 between the first wall surface 51 and one side of the negative electrode current collector in the layer forming section 50 and the distance D2 between the second wall surface 52 and the other side of the negative electrode current collector in the layer forming section 50 were 0.4 mm. Next, the negative electrode current collector that passed through the layer forming section 50 was passed through a drying furnace with a temperature of 110° C. for 10 minutes to volatilize the water contained in the negative electrode material paste. The dried negative electrode was cut into a rectangular shape of 50 mm×60 mm to obtain an unformed zinc battery negative electrode according to Example 1.

[0079] The thicknesses of the first and second negative electrode layers of the negative electrode according to Example 1 were measured. The thicknesses were measured at nine locations in FIG. 4, that is, at nine locations, the upper left corner a, the upper center b, the upper right corner c, the left center d, the center e, the right center f, the lower left corner g, the lower center h, and the lower right center i, when viewed from the lamination direction of the negative electrode, using a micrometer (PMU150-25MX, manufactured by Mitutoyo Corporation). The thicknesses at each location, the difference between the thickness of the first negative electrode layer and the thickness of the second negative electrode layer, and the ratio of the thickness of the second negative electrode layer to the thickness of the first negative electrode layer (thickness of the second negative electrode layer / thickness of the first negative electrode layer) are shown in Table 1.

[0080] <Creating a zinc battery> A lattice body made of foamed nickel with a porosity of 95% was prepared, and the lattice body was pressure-molded to obtain a positive electrode current collector. Next, a predetermined amount of cobalt-coated nickel hydroxide powder, metal cobalt, cobalt hydroxide, yttrium oxide, carboxymethylcellulose, polytetrafluoroethylene, and ion-exchanged water were weighed and mixed, and the mixed liquid was stirred to prepare a positive electrode material paste. At this time, the mass ratio of the solid content was adjusted to "nickel hydroxide: metal cobalt: yttrium oxide: cobalt hydroxide: carboxymethylcellulose: polytetrafluoroethylene = 88: 10.3: 1: 0.3: 0.3: 0.1". The moisture content of the positive electrode material paste was adjusted to 27.5 mass% based on the total mass of the positive electrode material paste. Next, the positive electrode material paste was applied to both sides of the positive electrode current collector, and then dried at 80 ° C. for 30 minutes. After that, it was pressure-molded with a roll press to obtain an unformed positive electrode having a positive electrode material layer.

[0081] For the separator, UP3355 (manufactured by Ube Industries, product name, air permeability: 440 seconds / 100 mL) was used as the microporous membrane, and nonwoven fabric (manufactured by Nippon Kodoshi Kogyo Co., Ltd., product name: VL-100, air permeability: 0.3 seconds / 100 mL) was used as the nonwoven fabric. The microporous membrane was hydrophilized with a surfactant Triton-X100 (manufactured by Sigma-Aldrich Japan LLC) before the battery was assembled. The hydrophilization was performed by immersing the microporous membrane in an aqueous solution containing 1% by mass of Triton-X100 for 24 hours, and then drying at room temperature for 1 hour. The air permeability of the microporous membrane indicates the value after the hydrophilization. Furthermore, the microporous membrane was cut to a predetermined size, folded in half, and processed into a bag shape by heat welding the sides. The nonwoven fabric was cut to a predetermined size.

[0082] A positive electrode and a negative electrode were housed in a microporous membrane processed into a bag shape. After laminating the positive electrode housed in the microporous membrane in a bag shape, the negative electrode housed in the microporous membrane in a bag shape, and the nonwoven fabric, the electrode plates of the same polarity were connected with a strap to prepare an electrode group (electrode plate group). The electrode group had 11 positive electrodes and 12 negative electrodes, and a nonwoven fabric was placed between each of the positive and negative electrodes (between the microporous membrane on the positive electrode side and the microporous membrane on the negative electrode side). After placing this electrode group in a battery case, a lid was attached to the top of the battery case, and the electrolyte was poured into the battery case to obtain an unformed nickel-zinc battery. Thereafter, charging was performed under the conditions of 800 mA and 15 hours to prepare a nickel-zinc battery with a nominal capacity of 8000 mAh.

[0083] Comparative Example 1 <Preparation of negative electrode for zinc battery> An unformed zinc battery negative electrode manufactured by a conventional method was prepared. This negative electrode was manufactured by applying a negative electrode material paste to both sides of the negative electrode current collector, and then passing the negative electrode current collector 22, both sides of which were coated with the negative electrode material paste, through the gap 53 while bringing the applied negative electrode material pastes 23a and 23b into contact with the first wall surface 51 or the second wall surface 52. The process itself is the same as in Example 1, but the ratio of the distance D2 between the second wall surface 52 and the other surface 21b of the negative electrode current collector 21 to the distance D1 between the first wall surface 51 and one surface 21a of the negative electrode current collector 21 was not adjusted, and the negative electrode current collector was visually arranged so that it was located near the center of the gap 53.

[0084] The thicknesses of the first and second negative electrode material layers were measured in the same manner as in Example 1. Table 1 shows the thickness at each location, the difference between the thickness of the first negative electrode material layer and the thickness of the second negative electrode material layer, and the ratio of the thickness of the second negative electrode material layer to the thickness of the first negative electrode material layer (thickness of the second negative electrode material layer / thickness of the first negative electrode material layer).

[0085] <Creating a zinc battery> A nickel-zinc battery was produced in the same manner as in Example 1, except that the negative electrode in Example 1 was changed to the negative electrode according to Comparative Example 1 described above.

[0086] <Evaluation of life performance> The nickel-zinc battery was charged at 25°C, 8000mA (1C), and a constant voltage of 1.9V until the current value attenuated to 400mA (0.05C), and then discharged at a constant current of 8000mA (1C) until the battery voltage reached 1.1V, which constituted one cycle. The test was terminated when the discharge capacity was below 60% of the discharge capacity of the first cycle, and the cycle life performance was evaluated based on the number of cycles performed until the end of the test. The number of cycles performed until the end of the test is shown in Table 1. As shown in Table 1, the nickel-zinc battery according to Example 1 had an increased number of cycles and was excellent in life performance compared to the nickel-zinc battery according to Comparative Example 1.

[0087] [Table 1] [Explanation of symbols]

[0088] 21...negative electrode current collector, 21a...one side of negative electrode current collector, 21b...other side of negative electrode current collector, 50...layer forming portion, 51...first wall surface, 52...second wall surface, 23a, 23b...negative electrode material paste, 24...negative electrode (negative electrode for zinc battery).

Claims

1. A method for producing a double-sided coated type negative electrode for a zinc secondary battery, the method comprising: a negative electrode current collector; a first negative electrode material layer provided on one side of the negative electrode current collector; and a second negative electrode material layer provided on the other side of the negative electrode current collector, a negative electrode material layer forming step of passing the negative electrode current collector between the first wall surface and the second wall surface while contacting the negative electrode material paste on both surfaces of the negative electrode current collector with a first wall surface and a second wall surface opposed to each other, and then passing the negative electrode current collector through a drying furnace to form the first negative electrode material layer and the second negative electrode material layer, in the negative electrode material layer forming step, a ratio of a distance between the second wall surface and the other surface of the negative electrode current collector to a distance between the first wall surface and the one surface of the negative electrode current collector is 0.7 to 1; a difference between a distance between the first wall surface and the one surface of the negative electrode current collector and a distance between the second wall surface and the other surface of the negative electrode current collector is 0.03 mm or less; The method for producing a negative electrode for a zinc secondary battery, wherein the temperature in the drying oven is 90 to 150° C.

2. The method for producing a negative electrode for a zinc secondary battery according to claim 1 , wherein the ratio is less than 1.

3. The method for producing a negative electrode for a zinc secondary battery according to claim 1 or 2, wherein the time for passing the negative electrode current collector through the drying oven is 1 to 60 minutes.

Citation Information

Patent Citations

  • Method of manufacturing negative electrode for enclosed alkaline storage battery

    JP1977151833A

  • Niizn battery

    JP1980090078A

  • Cylindrical alkaline zinc storage battery

    JP1986077255A

  • Coating device and its method for use

    JP1989194265A

  • Manufacturing device for zinc plate of alkaline zinc storage battery

    JP1995094175A